2021
DOI: 10.5194/bg-18-2347-2021
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria blooms in the Baltic Sea: a review of models and facts

Abstract: Abstract. The ecosystem of the Baltic Sea is endangered by eutrophication. This has triggered expensive international management efforts. Some of these efforts are impeded by natural processes such as nitrogen-fixing cyanobacteria blooms that add bioavailable nitrogen to the already over-fertilized system and thereby enhance primary production, export of organic matter to depth, and associated oxygen consumption. Controls of cyanobacteria blooms are not comprehensively understood, and this adds to the uncertai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 269 publications
(411 reference statements)
1
25
0
Order By: Relevance
“…The summer cyanobacteria bloom in the Baltic proper, and increasingly in recent years in the Bothnian Sea, is considered one of the main problems of Baltic Sea eutrophication, and the nitrogen fixation it carries out is an important process in Baltic ecosystem models (Munkes et al, 2021). It has long been considered limited by the availability of phosphorus (Larsson et al, 1985;Granéli et al, 1990).…”
Section: Lower Trophic Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The summer cyanobacteria bloom in the Baltic proper, and increasingly in recent years in the Bothnian Sea, is considered one of the main problems of Baltic Sea eutrophication, and the nitrogen fixation it carries out is an important process in Baltic ecosystem models (Munkes et al, 2021). It has long been considered limited by the availability of phosphorus (Larsson et al, 1985;Granéli et al, 1990).…”
Section: Lower Trophic Levelsmentioning
confidence: 99%
“…Are sediment trap measurements gross underestimates, or are there unidentified sites of denitrification or other overlooked nitrogen sinks in the water column? Nitrogen fixation is a central process in Baltic ecosystem models, and better observationally based estimates of processes in the nitrogen cycle are required for assessing their credibility (Munkes et al, 2021).…”
Section: Lower Trophic Levelsmentioning
confidence: 99%
“…This indicates that acid rain has an adverse effect on surrounding ecosystems Experimental study, CC effects on causative agent [ 39 ] Wu et al, 2014 China Temperature and heavy rainfall frequency Water quality In Beijing, the undergoing increased temperature and heavy rainfall frequency affect water quality related to fluoride and arsenic concentrations of most urban lakes, that becoming worse under climate change trend Cross-section study, CC effects on causative agent [ 40 ] Dorbac et al 2016 Serbia High temperature Water and fish samples Sampling of the water and fish (common carp, ( Cyprinus carpio ) was performed. and were found to contain saxitoxin, microcystin, and/or nodularin Cross-section study, CC effects on causative agent [ 41 ] Lad et al, 2019 Microcystin-LR (MC-LR) Mice Exposure to MC-LR at levels that results in significant exacerbation of hepatic injury Experimental study, CC effects on causative agent, and liver diseases [ 44 ] Munkes et al, 2021 Baltic Sea Global warming Cyanobacteria (CyanoHAB) There is a synergism between global warming and eutrophication, that simultaneously intensification of CyanoHAB Review, CC effects on causative agent [ 46 ] Lürling et al, 2018 Global Global warming Surface water and cyanobacteria Global warming stimulates growth of hepatotoxic cyanobacteria and increase the cellular toxicity levels directly and indirectly Experimental study, CC effects on causative agent [ 47 ] El-Shehawy et al, 2012 Global Global warming …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, high atmospheric temperature leads to increase in the stratification and lowers the viscosity of seawater which is favorable to CyanoHAB growth [ 40 ]. Thus, there is a synergism between global warming and eutrophication, which is simultaneous with intensification of CyanoHAB [ 44 ]. It has been reported, in a multi-lake analysis, that cyanobacteria appeared more sensitive to the interaction of nutrients and temperature in more eutrophic lakes [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we have used a CLC model that includes benthic and pelagic akinetes from which the summer blooms originate. Research has shown that the life cycles of the different major bloom forming taxa are complex and there is no single answer on how they start growing after winter (Munkes et al 2021). Experiments have suggested that all taxa form akinetes to some extent but the summer bloom of Nodularia spumigena and Aphanizomenon sp.…”
Section: Discussionmentioning
confidence: 99%